Les deux derniers volets de la trilogie mozartienne de Maurice Sendak : Chère Mili et On est tous dans la gadoue suivi de Jack et Guy. - Gaëlle Levesque (Strenae)
Mozart plays the intermediary between three picture books by Maurice Sendak: Outside Over There, Dear Mili, and We Are All in the Dumps with Jack and Guy, in which Mozart is explicitly depicted. This article focuses on the last two works of this trilogy, highlighting their points in common. Although Mozart's music is heard differently in Dear Mili and We Are All in the Dumps—mostly through the setting in the first picture book where the characters are mute, and through an almost opera-like construction in the second—it has the same purpose of salvation. In addition to referencing paintings, both picture books share dark issues that the children are forced to cope with alone, particularly in relation to the Holocaust.